LncRNA cardiac autophagy inhibitory factor is downregulated in rheumatoid arthritis and suppresses the apoptosis of fibroblast-like synoviocytes by promoting the maturation of miRNA-20a - Dongming Xu,; Ling Lin,; Zhen Chen, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to investigate the effects of LncRNA cardiac autophagy inhibitory factor (CAIF) and miR-20a on the apoptosis of synovial cells in rheumatoid arthritis (RA) and the regulatory mechanism. Patients and methods: Between May 2018 and March 2020, a total of 62 RA patients (24 males, 38 females; mean age: 55.2±4.9 years; range, 42 to 68 years) and 62 controls (24 males, 38 females; mean age: 55.3±4.8 years; range, 41 to 68 years) were included in this study. Plasma samples were collected from all participants. The expression levels of CAIF, mature miR-20a, and miR-20a precursor in these plasma samples were determined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Correlations were analyzed using linear regression analysis. Overexpression of CAIF was achieved in human fibroblast-like synoviocytes (HFLSs) and the expression levels of mature miR-20a and miR-20a precursor were determined using RT-qPCR. Cell apoptosis was analyzed by cell apoptosis assay. Results: The CAIF was downregulated in RA and positively correlated with the expression of mature miR-20a. In HFLSs, LPS treatment resulted in downregulation of both CAIF and miR-20a in a dose-dependent manner. In HFLSs, overexpression of CAIF did not affect the expression of miR-20a precursor, but upregulated the expression of mature miR-20a. Cell apoptosis analysis showed that overexpression of CAIF and miR-20a inhibited the apoptosis of HFLSs induced by LPS. The combination of overexpression of CAIF and miR-20a showed a stronger effect. Conclusion: The CAIF may suppress the apoptosis of HFLSs in RA by promoting the maturation of miR-20a.